Salicylic Acid Seed Priming: A Key Frontier in Conferring Salt Stress Tolerance in Barley Seed Germination and Seedling Growth - Rim Ben Youssef; Nahida Jelali; Jose Ramón Acosta Motos; Chedly Abdelly; Alfonso Albacete (Agronomy)
The goal of the current study was to investigate the effects of seed priming with salicylic acid (SA) on seed germination parameters, seedling growth traits, nutritional element mobilization, and oxidative stress status in two barley species that were subjected to various salt treatments. The findings demonstrated that salinity reduced a number of germination parameters in unprimed seeds and impacted seedling growth by impeding both species’ necessary nutrient mobilization. Under this abiotic stress, a noticeable rise in malondialdehyde and electrolyte leakage was also noted. Interestingly, pretreating seeds with SA improved seed germination and seedling growth performance under either 100 mM or 200 mM NaCl treatments. In fact, SA improved the length and dry weight of stressed seedlings of both barley species in addition to increasing the germination rate and mean daily germination. Additionally, SA increased the content of calcium, iron, magnesium, and potassium while lowering the concentrations of sodium and malondialdehyde and electrolyte leakage. It is significant to note that, in comparison to Hordeum maritimum, the positive effects of this hormone were more noticeable in stressed Hordeum vulgare species.